The Romanian Curriculum of Early Education and Primary Education - FLORENTINA-LAVINIA, MATEI (Journal of Education, Society & Multiculturalism, 2022)
The article analyzes the Romanian curriculum specific to primary and preschool education. The article focuses on the curriculum approved in 2011 for primary education, respectively the one approved in 2019 for early education. The analysis between the primary education curriculum and the early education curriculum follows the specifics of the curriculum, the purpose, the values promoted, the focus on the formation of the respective behavioral competencies. The analysis is performed on the basis of the educational policy documents elaborated by the Institute of Education Sciences and on the official curricular documents elaborated and approved by the Romanian Ministry of National Education.